2014
DOI: 10.1007/s10549-014-2913-y
|View full text |Cite
|
Sign up to set email alerts
|

Expression of organic anion-transporting polypeptide 1A2 and organic cation transporter 6 as a predictor of pathologic response to neoadjuvant chemotherapy in triple negative breast cancer

Abstract: Organic anion-transporting polypeptide 1A2 (OATP1A2) and organic cation transporter 6 (OCT6) are involved in the uptake of taxanes and anthracyclines, respectively. The aim of this study was to evaluate expression levels of OATP1A2 and OCT6 as a predictor of response to neoadjuvant chemotherapy (NAC) in breast cancer. A total of 124 patients who received anthracycline/taxane-based NAC were included. Expression levels of OATP1A2 and OCT6 were immunohistochemically assessed in core needle biopsies obtained prior… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 26 publications
1
9
0
Order By: Relevance
“…However, increased OATP expression may also make breast tumors more susceptible to chemotherapeutic agents that are transported by that OATP, as was suggested in a study where OATP1B3 expression was associated with improved prognosis in estrogen receptor positive patients only, possibly due to increased uptake of tamoxifen in these patients (Muto et al, 2007). Recently, it has been shown that OATP1A2 expression may predict pathologic response to neoadjuvant chemotherapy in triple-negative breast cancer patients as well (Hashimoto et al, 2014).…”
Section: Oatp Expression In Tumor Tissues and Theirmentioning
confidence: 97%
“…However, increased OATP expression may also make breast tumors more susceptible to chemotherapeutic agents that are transported by that OATP, as was suggested in a study where OATP1B3 expression was associated with improved prognosis in estrogen receptor positive patients only, possibly due to increased uptake of tamoxifen in these patients (Muto et al, 2007). Recently, it has been shown that OATP1A2 expression may predict pathologic response to neoadjuvant chemotherapy in triple-negative breast cancer patients as well (Hashimoto et al, 2014).…”
Section: Oatp Expression In Tumor Tissues and Theirmentioning
confidence: 97%
“…Thus, it is plausible that its efficacy in breast cancer treatment could be related to the fact that doxorubicin is an excellent OATP1A2 substrate and hence would preferentially accumulate in breast cancer cells due to OATP1A2 overexpression. Indeed, a recent study in breast cancer patients indicated those tumors with high expression of OATP1A2 was an independent predictor of good pathologic response to anthracycline-and taxane-based chemotherapy (Hashimoto et al, 2014). This merits further investigation because these data would suggest that OATPs may be an appropriate drug target when overexpressed in tumor tissues as chemotherapeutic agents that are good Fig.…”
Section: Oatps and Doxorubicin Dispositionmentioning
confidence: 98%
“…Interestingly, Miki et al also reported a significant correlation between the expression of OATP1A2 and the nuclear receptor PXR (pregnane X receptor), providing possible insights into the regulation of OATP1A2 expression (61) (14). In the clinical setting, the expression of OATP1A2 combined with another transporter OCT6 in patients with triple-negative breast cancer (which displays no detectable expression for estrogen receptor, progesterone receptor, and Her2/neu and has very poor prognosis) was predictive of response to anthracycline/ taxane-based neoadjuvant chemotherapy (96). Further investigations will be required to evaluate the clinical relevance of these findings in patients with hormone-dependent or triplenegative breast cancers.…”
Section: Oatp1a2 (Gene Symbol Slco1a2)mentioning
confidence: 99%